Teachers' talk regarding inclusion: a comparative discursive study - Bomela, Yolisa Faith (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
Much research on the educators' perceptions of and attitudes towards inclusive education has been conducted both in South Africa and abroad. What is absent in this literature is an acknowledgement of the socially constructed nature of teachers' responses to inclusive education and its recipients. In this study, the talk of educators involved in piloting inclusive education is compared to that of educators who are not involved, in order to determine the discourses from which educators draw in their construction of inclusive education. It is a comparative study premised on the social constructionist perspective in which discourse analysis was employed. The sample was drawn from schools piloting inclusive education in the East London District of the Eastern Cape Province in South Africa and was compared with schools not involved in the pilot, but in the same area. Semi- structured interviews were conducted with eight educators spread across two piloting and two non piloting schools. The analysis revealed significant similarities and quite minimal differences in the manner in which educators across the two settings construct their experiences of inclusive education. Even though the educators draw on the rights driven anti-discriminatory discourse, they still embrace the special needs/medical/expertise and charity discourses. These discourses construct disability around notions of disputed degrees of impairment, feared status and perceptions of disability as a personal issue rather than a public responsibility, and they undermine the status of people with a disability while supporting notions of dependency. In this article, I will argue that the historical legacy within which these discourses were originally constructed, will essentially continue unless there is a change in how diversity is viewed.
Keywords: Uncatalogued